The quantity–quality fertility–education trade-off - Haoming Liu (IZA World of Labor, 2015)
At the national level, it has long been observed that a country's average education level is negatively associated with its total fertility rate. At the household level, it has also been well documented that children's education is negatively associated with the number of children in the family. Do these observations imply a causal relationship between the number of children and the average education level (the quantity–quality trade-off)? A clear answer to this question will help both policymakers and researchers evaluate the total benefit of family planning policies, both policies to lower fertility and policies to boost it.
Keywords: J13; N3; 330; demographic transition; fertility; education; child quality; quantity–quality trade-off